Shelf life of fresh-cut yellow carrot as affected by chitosan or locust bean gum edible coatings - Chiara Alessandra Carmen Rutigliano; Claudio Cannata; Federico Basile; Guglielmo Fichera; Giuseppe Muratore; Cristina Restuccia; Leo Sabatino; Emanuele La Bella; Cherubino Leonardi; Rosario Paolo Mauro (Journal of Agriculture and Food Research, 2025)
Recently, consumer interest in yellow carrots has been increasing. However, there is currently no available literature on the postharvest behavior of fresh-cut yellow carrots or on the potential of edible coatings in mitigating their quality alteration during shelf life. The present experiment addressed the postharvest evolution of compositional and microbial traits in ready-to-eat yellow carrot (“Mello Yello’) slices stored for 0, 4, and 8 days (S0, S4, and S8, respectively) at 4.0 °C, either uncoated (control) or coated with chitosan (CH, 2 % w/v) or locust bean gum (LBG, 1 % w/v). The LBG-coated slices showed the lowest weight loss (3.27 g kg−1 fresh weight, FW), while CH best preserved the visual quality of carrots, as indicated by their lowest whiteness index (39.0) and total color difference (1.31). At S8, coated samples had higher total sugars (501 g kg−1 dry weight, DW), carotenoids (181 mg kg−1 DW), and antioxidant activity (76.8 mmol Trolox equivalents kg−1 DW) than control. At the end of the storage, CH was the most effective in reducing the microbial decay of carrots, whereas LBG best preserved their ascorbic acid content (263 mg kg−1 DW). Overall, our results highlight both pros and cons of the tested coatings, with the preservation of ascorbic acid content (in the case of CH) and the maintenance of visual appearance and antimicrobial properties (in the case of LBG) emerging as key aspects to enhance their performance in improving the quality of the tested yellow carrot during shelf life.